The Impact of Internal-External Factors in Antenatal Care Service on the Effort of Public Health Center in Agam Regency to Accelerate Minimum Service Standard Achievement - Bismihayati Bismihayati; Aldri Frinaldi; Rembrandt Rembrandt; Dasman Lanin; Genius Umar (Pascasarjana, Universitas Negeri Padang, 2022)
Reducing maternal mortality is Indonesia's main goal for improving health. By offering high-quality antenatal care services at least four times during pregnancy with the 10T standard, efforts are made to reduce maternal mortality. In the Minister of Health Regulation No. 4/2019 concerning Minimum Service Standards (MSS) in the Health Sector, it is stated that antenatal care services are influenced by two factors. elements: internal and external. Internal factors are factors related to a person's personality and external factors are factors that influence behavior and are influenced by the environment. This research method is quantitative with a sample of 69 pregnant women in the third trimester taken by purposive sampling using questionnaires and univariate, bivariate and multivariate data analysis techniques. According to research findings, knowledge is the most powerful factor influencing various antenatal care services. The author advises local governments to promote understanding and support from husbands for pregnant women, especially through the